Comics, Culture, and Religion (Bloomsbury Academic, 2023)
This open access book offers an overview of the relations between comics and religion from the perspective of cultural sociology. How do comics function in religions and how does religion appear in comics? And how do graphic narratives inform us about contemporary society and the changing role of religion? Contributing scholars use international examples to explore the diversity of religions, spirituality, and dispersed notions of the sacred, including Christianity, Islam, Judaism, Zoroastrianism, Indian, and Japanese religions. In addition, the rituals, ethics, and worldviews that surface in the comics milieu are discussed. With the growing popularity and influence of comics and graphic novels in contemporary culture, this book provides a valuable addition to the discussion of the medium, focusing on religious and sociological aspects. A rich resource for both students and scholars in popular culture, media studies, and religion. The ebook editions of this book are available open access under a CC BY-NC-ND 4.0 license on www.bloomsburycollections.com. Open access was funded by The Faculty for Humanities and Education and the University Library at the University of Agder, Norway.